2008
DOI: 10.1523/jneurosci.0578-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Size and Spatial Coding

Abstract: Images of the same physical dimensions on the retina can appear to represent different-sized objects. One reason for this is that the human visual system can take viewing distance into account when judging apparent size. Sequentially presented images can also prompt spatial coding interactions. Here we show, using a spatial coding phenomenon (the tilt aftereffect) in tandem with viewing distance cues, that the tuning of such interactions is not simply determined by the physical dimensions of retinal input. Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Similar mechanisms might hold beyond the retina as well. For example, perceived size appears to be represented in early visual cortex (Arnold, Birt, & Wallis, 2008; Murray, Boyaci, & Kersten, 2006), and population coding of object size could also give rise to ensemble coding of average size. Along these lines, Im and Chong (2009) reported that the mean sizes of sets of target circles embedded in rings of smaller or larger surrounding circles were perceived as a function of the Ebbinghaus illusion induced by the surrounding circles, and not based on the physical sizes of the target circles.…”
Section: Discussionmentioning
confidence: 99%
“…Similar mechanisms might hold beyond the retina as well. For example, perceived size appears to be represented in early visual cortex (Arnold, Birt, & Wallis, 2008; Murray, Boyaci, & Kersten, 2006), and population coding of object size could also give rise to ensemble coding of average size. Along these lines, Im and Chong (2009) reported that the mean sizes of sets of target circles embedded in rings of smaller or larger surrounding circles were perceived as a function of the Ebbinghaus illusion induced by the surrounding circles, and not based on the physical sizes of the target circles.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Arnold et al (2008) found that perceived size could influence the spatial profile of the TAE. Similarly, our results suggest that the spatial location of the TAE is influenced by the perceived location of the adaptor when it is shifted by a motion-based illusion.…”
Section: Discussionmentioning
confidence: 99%
“…This selectivity of the TAE appears to be largely dependent on the match between the retinotopic locations of the adaptor and test stimuli (Boi,Öğmen, & Herzog, 2011; Knapen, Rolfs, Wexler, & Cavanagh, 2010), though there were earlier reports of spatiotopic transfer of the TAE across saccades (Melcher, 2005). Intriguingly, Arnold, Birt, and Wallis (2008) demonstrated that the TAE can be influenced by an illusion of perceived size. In their experiment, they manipulated distance cues to influence the perceived size of an adapting stimulus and showed that the perceptual overlap between the adapting and test grating could bias the direction of the TAE.…”
Section: Introductionmentioning
confidence: 99%
“…In this illusion, the size of the moon appears bigger when it is viewed near the horizon and smaller when it is at the top of the sky. Previous explorations were based on the retinal images and spatial code interactions and led the authors suppose that spatial coding mechanisms modulate the retina output [4] and in the absence of contextual references the retinal circuity had less *Address correspondence to this author to the Departamento de Psicologia Experimental, Instituto de Psicologia USP, Av. Prof. Mello Moraes, 1721, 05338-030, Butantã, São Paulo, SP, Brasil; Tel: +55 11 3091 1918; E-mail: costamf@usp.br information to compare spatially and the output to the visual cortex were biased.…”
Section: Introductionmentioning
confidence: 99%